Correlation Between Learning Motivation And Student Self-Adjustment - Rani Violita; Dina Sukma (Jurnal Neo Konseling, 2021)
This research is motivated by a phenomenon that exists in junior high schools. The phenomenon that occurs is in the form of difficulty in understanding the material due to differences in the different learning processes between elementary and junior high schools. This transitional period affects student learning motivation. therefore, students are required to be able to adapt to the new environment in order to be able to achieve good learning outcomes and optimal self-development. This study aims to describe learning motivation, describe student adjustment and examine the relationship between learning motivation and student adjustment.The research method used is descriptive and correlational approaches. The population of this study were students of class VIII at SMP Negeri 38 Padang, totaling 216 students. The number of samples in this study was 153 students. Sampling using Simple Random Sampling technique. Data were analyzed using descriptive analysis techniques and correlational analysis, testing the research hypothesis using the Pearson Product Moment correlation formula. The results showed that: (1) students' learning motivation was in the high category, (2) students' adjustment was in the high category, (3) there was a significant positive relationship between learning motivation and students' adjustment with a correlation of 0.859 with a very strong category at significance level of 0.000. Thus the counseling teacher can maintain and improve student learning motivation and student adjustment by using guidance and counseling services for students.